Control of Mitochondrial Activity by the Ubiquitin Code in Health and Cancer - Laura Rinaldi; Emanuela Senatore; Rosa Iannucci; Francesco Chiuso; Antonio Feliciello (Cells, 2023)
Cellular homeostasis is tightly connected to the broad variety of mitochondrial functions. To stay healthy, cells need a constant supply of nutrients, energy production and antioxidants defenses, undergoing programmed death when a serious, irreversible damage occurs. The key element of a functional integration of all these processes is the correct crosstalk between cell signaling and mitochondrial activities. Once this crosstalk is interrupted, the cell is not able to communicate its needs to mitochondria, resulting in oxidative stress and development of pathological conditions. Conversely, dysfunctional mitochondria may affect cell viability, even in the presence of nutrients supply and energy production, indicating the existence of feed-back control mechanisms between mitochondria and other cellular compartments. The ubiquitin proteasome system (UPS) is a multi-step biochemical pathway that, through the conjugation of ubiquitin moieties to specific protein substrates, controls cellular proteostasis and signaling, removing damaged or aged proteins that might otherwise accumulate and affect cell viability. In response to specific needs or changed extracellular microenvironment, the UPS modulates the turnover of mitochondrial proteins, thus influencing the organelle shape, dynamics and function. Alterations of the dynamic and reciprocal regulation between mitochondria and UPS underpin genetic and proliferative disorders. This review focuses on the mitochondrial metabolism and activities supervised by UPS and examines how deregulation of this control mechanism results in proliferative disorders and cancer.